Perkampungan Tua Bius Tipang, Kecamatan Baktiraja, Kabupaten Humbang Hasundutan: Kajian Antropolingustik - Romaida Sihite; Robert Sibarani (Journal of Language Development and Linguistics, 2022)
This thesis is entitled "The Old Village of Bius Tipang, Baktiraja District, Humbang Hasundutan Regency: Anthropology Studies". This study aims to describe Horja and Bius, 1) the form of the Bius Tipang village, the social values and norms that exist in the Bius Tipang Old Village. The method used in this research is the qualitative method. The results obtained from this study, namely the anthropological values that exist in the old village of Bius Tipang are: (1) The community believes that there is a fence that protects them from harm or evil intentions. (2) the existence of bamboo which has the power which is believed to be the guardian of the village.